“If you are circumcised, you are the best”: Understandings and perceptions of voluntary medical male circumcision among men from KwaZulu-Natal, South Africa - Humphries, Hilton (Cult Health Sex, 2015)
While the uptake of voluntary medical male circumcision (VMMC) is increasing, South Africa has only attained 20% of its target to circumcise 80% of adult men by 2015. Understanding the factors influencing uptake is essential to meeting these targets. This qualitative study reports on findings from focus group discussions with men in rural KwaZulu-Natal, South Africa about what factors influence their perceptions of VMMC. The study found that VMMC is linked to perceptions of masculinity and male gender identity including sexual health, sexual performance and pleasure, possible risk compensation and self-identity. Findings highlight the need to understand how these perceptions of sexual health and performance affect men’s decisions to undergo circumcision and the implications for uptake of VMMC. The study also highlights the need for individualised and contextualised information and counselling that can identify, understand and address the perceptions men have of VMMC, and the impacts they believe it will have on them.